2015
DOI: 10.1097/sla.0000000000001445
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Malabsorption and Malnutrition After Esophageal and Gastric Cancer Surgery

Abstract: Malabsorption and malnutrition are prevalent in survivorship of esophageal and stomach cancer. This may be underappreciated, and both gut and pancreatic insufficiency represent modifiable targets in the interdisciplinary approach to recovery of HR-QL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 34 publications
4
122
1
4
Order By: Relevance
“…In the present study, severe diarrhoea was more common in the group of patients with >10% BWL (13% versus 0%). In a recent systematic study of a prospective consecutive series of 45 disease-free patients after esophagectomy or gastrectomy, Henegham et al (16) found that the incidence of malabsorption at 18 to 24 months postoperatively was 71% in the gastrectomy group. The proportion of patients with Climent 11 more than 15% weight loss had significantly lower nutritional risk index scores, and a higher incidence of malabsorption compared with those who had less than 15% weight loss at 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, severe diarrhoea was more common in the group of patients with >10% BWL (13% versus 0%). In a recent systematic study of a prospective consecutive series of 45 disease-free patients after esophagectomy or gastrectomy, Henegham et al (16) found that the incidence of malabsorption at 18 to 24 months postoperatively was 71% in the gastrectomy group. The proportion of patients with Climent 11 more than 15% weight loss had significantly lower nutritional risk index scores, and a higher incidence of malabsorption compared with those who had less than 15% weight loss at 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, a cut-off of 10% was chosen because this percentage of BWL is considered as a severe nutritional risk marker (12)(13)(14)16). Mean scores and 95% confidence intervals (CIs) for HRQL were calculated preoperatively and at 2 years after surgery.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that an increased level of CRP may be associated with poorer prognosis in patients with tumors, including ovarian cancer, penile cancer and non-small cell lung cancer (36)(37)(38). In addition, malabsorption and malnutrition may be associated with decreased survival time in various tumors, including esophageal squamous cell carcinomas and endometrial cancer (39,40). In a previous study, Alb was used to estimate nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Alb was used to estimate nutritional status. For patients with GC, protein digestion and absorption were decreased, whereas protein metabolism was increased, resulting in a negative nitrogen balance (18,39). The CRP/Alb ratio is a useful prognostic indicator that was initially used to identify patients with serious conditions on an acute medical ward by Fairclough et al (41).…”
Section: Discussionmentioning
confidence: 99%